When Lawyers and Law Firms Invest in Their Corporate Clients' Stock - Donald C. Langevoort (Washington University Law Quarterly, 2002)
I am not convinced that lawyers’ investments in clients in lieu of fees are problematic enough from a conflicts standpoint that the rules of professional responsibility should treat them as presumptively inconsistent with the lawyer’s fiduciary responsibility.
Keywords: Corporate lawyers; Stock options; Legal ethics; Insider trading in securities; Law firms